'n Evaluering van en antwoord op kritiek teen die Apostolicum - Verster, Pieter (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2025)
evaluation of and reply to criticism of the Apostolicum In churches all over the world, and also in South Africa, many confess their faith every Sunday with the Apostolicum or Twelve Articles. The latter are regarded as articles of the Christian faith based upon the proclamation of the apostles. Recently, Julian Müller’s book, Geloofsgesprekke in die Tsitsikamma (2022), loosely translated as ‘discussions about belief in the Tsitsikamma’, received attention in this regard. Müller challenges the concept that the Twelve Articles as a comprehensive confession are still relevant and acceptable. Further, Müller challenges beliefs pertaining to God as the Almighty Creator, Jesus’ resurrection, and other confessions of the Christian faith. The main reason for the suggestion that these confessions cannot be accepted, in his opinion, is because of the fact that we currently live with a new world view far different from that of Biblical times. He states that the cosmology of the ancient world has changed; a new cosmology is now present. In that sense, theism should be rejected; one should rather refer to panentheism. Müller’s views are steered by his post-foundationalist hermeneutics. This paper takes an oppositional stance to Müller’s position by emphasising the confession that God is an Almighty, loving Father and also that Jesus’ victorious resurrection from the death on the cross has meaning for all. This means that one should take into cognisance the wonders of God and of the gospel and proclaim it anew in a modern world. One should not regard the Twelve Articles as obsolete, but regard them as still very relevant in the world in which we live.